Kepemimpinan Transformasional Kepala Madrasah dalam Meningkatkan Kinerja Guru di Madrasah Darul Aitam Jerowaru: Transformational Leadership of the Principal in Improving Teacher Performance at Madrasah Darul Aitam Jerowaru - Sirajun Nasihin; Abd Qudus Al Badani; Muh. Zainil Rahman; Anton Irawan; Erwin Andani Putra (Pendidikan Al-Gafari, 2026)
Transformational leadership is a leadership style that is capable of bringing about major changes in an organization through a strong vision, moral encouragement, and active involvement in fostering and developing the potential of subordinates. This study aims to describe the form of transformational leadership of madrasah principals, supporting and inhibiting factors in its implementation, and the impact of such leadership on improving teacher performance. This study uses a qualitative approach. Data collection techniques were carried out through interviews, observation, and documentation. The results of the study indicate that madrasah principals implement transformational leadership through four main indicators, namely: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Supporting factors in the implementation of transformational leadership include support from teachers, a conducive work environment, and open communication between madrasah principals and teachers. The inhibiting factors are limited facilities and infrastructure and the high administrative burden on teachers. The impact of the madrasah principal's transformational leadership is seen in the improvement of discipline, responsibility, creativity, and collaboration of teachers in carrying out their duties.